American Pioneer Women Architect Lois Langhorst. Exhibition of Abstract Watercolors at Biosca Galleries at Madrid (1955) - Salazar Lozano, Maria Del Pilar (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
In June 1955, several reviews were published in Madrid in magazines and newspapers about an exhibition of watercolors at the Biosca galleries. The author has an unknown name: Lois Langhorst; and the watercolor presented a marked and innovative abstract character. Among the names of the artists who exhibited in this gallery they hardly appear foreigners. The story behind this exhibition takes us to the construction of the American bases in Spain and from there to the trajectory of one of the pioneering American woman architects in the profession. This article aims to clarify the unknowns that this exhibition presents, delving into the complexity of being a female architect at the time. It seeks to expose Lois Langhorst's stay in Spain and the contacts that she and her husband, Frederick Langhorst, had with Spanish society in mid-century Madrid.
Keywords: Woman Architect; Abstract Expresionism; Spanish Architecture; United States of America; Franco’s Regime